A Role for HAPLN1 During Phenotypic Modulation of Human Lung Fibroblasts In Vitro. (November 2020) - Evanko, Stephen P.; Gooden, Michel D.; Kang, Inkyung; Chan, Christina K.; Vernon, Robert B.; Wight, Thomas N.
Hyaluronan and proteoglycan link protein 1 (HAPLN1) stabilizes interactions between two important extracellular matrix (ECM) macromolecules, versican and hyaluronan, which facilitate proliferation of fibroblasts and their conversion to myofibroblasts. However, the role of HAPLN1 in these events has not been studied. Using immunocytochemistry, cellular and ECM locations of HAPLN1 were evaluated in cultured human lung fibroblasts during proliferation and conversion to myofibroblasts. HAPLN1 localized to pericellular matrices, associating with both versican and hyaluronan in the ECM and on the cell surface. Nuclear and total HAPLN1 immunostaining increased after myofibroblast induction. Confocal microscopy showed HAPLN1 predominant in the ECM under cells while versican predominated above cells. Versican and HAPLN1 were also juxtaposed in columnar inclusions in the cytoplasm and nucleus. Nuclear HAPLN1 staining in interphase cells redistributed to the cytosol during mitosis. In the absence of TGF-β1, addition of exogenous bovine HAPLN1 (together with aggrecan G1) facilitated myofibroblast formation, as seen by significant upregulation of α-smooth muscle actin (SMA) staining, while adding full-length bovine versican had no effect. Increased compaction of hyaluronan-rich ECM suggests that HAPLN1 plus G1 addition affects hyaluronan networks and myofibroblast formation. These observations demonstrate changes in both extracellular and intracellular localization of HAPLN1 during fibroblast proliferation and myofibroblast conversion suggesting a possible role in fibrotic remodeling: